The Macroscopic and Radiographic Skull and Dental Pathology of the Tasmanian Devil (Sarcophilus harrisii) - Landy, Shanna; Peralta, Santiago; Vogelnest, Larry; Fiani, Nadine (Frontiers in Veterinary Science, 2021)
While the gross skull and dental morphology, masticatory biomechanics, dental eruption patterns, and radiographic dental anatomy has been described in the Tasmanian devil (Sarcophilus harrisii ), to date no studies have comprehensively examined the prevalence and appearance of pathologic processes affecting their skulls and dentition. As such, the aim of this study was to describe macroscopic and radiographic anatomy and identify the prevalence of anatomic variations and pathological processes in Tasmanian devil dentition and skulls. To do so, anatomical and pathological findings were documented in Sarcophilus harrisii skulls using photography and dental radiography. Assessment of skull trauma, anatomical and developmental abnormalities, periodontitis, endodontic disease, and tooth resorption was performed. A total of 28 Sarcophilus harrisii skulls containing 1,028 teeth were examined. Evidence of postmortem trauma was common. The most common positional abnormality was palatal or buccal rotation of the premolar teeth. While the alveolar bone margin was commonly positioned apically to the cementoenamel junction (98.2%), only 14.2% demonstrated evidence of periodontitis. Tooth fractures were common, affecting 27 skulls, however radiographic signs of endodontic disease were only noted 4.5% of affected teeth, as was non-inflammatory root resorption (2.0%). A wider root canal width, which was used as a criterion for age determination, was associated with smaller skull dimensions, incompletely erupted teeth, and subjectively less fusion of the mandibular symphysis. Through an improved understanding of what constitutes normal anatomy and the appearance and frequency of pathologic processes that affect the skulls and teeth, this knowledge can help develop a foundation for understanding the oral health and management of live animals for this endangered species.